2011
DOI: 10.1080/01431161.2010.512943
|View full text |Cite
|
Sign up to set email alerts
|

Variation in aerosol black carbon concentration and its emission estimates at the mega-city Delhi

Abstract: Simultaneous measurements of aerosol black carbon (BC) mass concentration using an Aethalometer Model AE-42 and mixing layer height (MLH) using a monostatic sonic detection and ranging (SODAR) system were carried out from January 2006 to January 2007 at the mega-city Delhi. The BC concentration generally had a typical diurnal variation with morning and late-afternoon/night peaks. The average BC concentration during the whole period of observation was fairly high at 14.75 µg m −3 . The BC concentration nearly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 38 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…The daily mean BC concentration for the entire study period was found to vary between 4.2 and 70.5 µg m −3 at Delhi (with a mean of 23.5 ± 13.2 µg m −3 during the winter and 9.5 ± 3.0 µg m −3 during the spring), whereas it was found to be vary between 0.3 and 3.1 µg m −3 at Manora Peak (with a mean of 1.2 ± 0.8 µg m −3 during the winter and 1.4 ± 0.6 µg m −3 during the spring). The seasonal mean BC mass concentration of the present observations may be compared with another observations at Delhi during the year 2006 made by Bano et al (2011). They have observed the average BC concentration of 25.5 µg m −3 during the winter (December–February) and 9.4 µg m −3 during the summer (March–May).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The daily mean BC concentration for the entire study period was found to vary between 4.2 and 70.5 µg m −3 at Delhi (with a mean of 23.5 ± 13.2 µg m −3 during the winter and 9.5 ± 3.0 µg m −3 during the spring), whereas it was found to be vary between 0.3 and 3.1 µg m −3 at Manora Peak (with a mean of 1.2 ± 0.8 µg m −3 during the winter and 1.4 ± 0.6 µg m −3 during the spring). The seasonal mean BC mass concentration of the present observations may be compared with another observations at Delhi during the year 2006 made by Bano et al (2011). They have observed the average BC concentration of 25.5 µg m −3 during the winter (December–February) and 9.4 µg m −3 during the summer (March–May).…”
Section: Resultssupporting
confidence: 61%
“…Considering the key role they play in radiative forcing (Srivastava et al , 2012a), studies on BC aerosols have become an important topic. However, there are less data available on BC aerosols from the Indian region though a few studies have shown the characteristics of BC at different locations in India (Ramachandran and Rajesh, 2007; Dumka et al , 2010; Bano et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the large spatial heterogeneity of sources and emission strengths of BC over the Indian region, it is essential that the model simulations are compared and validated with the high‐resolution, ground‐based observations. Based on multiyear measurements, very high values of BC in winter are reported over the urban/metropolitan city areas, viz., Delhi (~25 µg m −3 [ Bano et al ., ]), Hyderabad (~13 µg m −3 [ Jose et al ., 2016]), Chennai (~12 µg m −3 [ Aruna et al ., ]), and Kolkata (~27 µg m −3 [ Talukdar et al ., ]), while BC concentrations of very low magnitude are reported over the remote continental and Himalayan locations [ Gogoi et al ., ]. Over the northeastern part of India, the observed values of BC mass concentrations >20 µg m −3 are quite significant considering the remote nature of the region.…”
Section: Discussionmentioning
confidence: 99%
“…The EBC concentration is significantly reduced during monsoon season associated with the wash out of EBC due to precipitation and scavenging effect of rainfall (Bano et al, 2011). The monthly variation of rainfall in the bottom panel of Fig.…”
Section: Seasonal Variationmentioning
confidence: 99%
“…However, seasonal mean values of EBC at Tripura are consistently lower than those at Delhi in all seasons. As Delhi is highly industrialized, densely populated and a city of high traffic density, the higher concentration over Delhi than Tripura may be attributed to the greater influence of anthropogenic sources such as vehicular and industrial emissions in the region (Bano et al, 2011).…”
Section: Seasonal Variationmentioning
confidence: 99%